2021
DOI: 10.3390/met11111671
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior Assessment of Ti-6Al-4V ELI Alloy Produced by Laser Powder Bed Fusion

Abstract: The present work correlates the quasi-static, tensile mechanical properties of additively manufactured Ti-6Al-4V extra low interstitial (ELI, Grade 23) alloy to the phase constituents, microstructure, and fracture surface characteristics that changed with post-heat treatment of stress relief (670 °C for 5 h) and hot isostatic pressing (HIP with 100 MPa at 920 °C for 2 h under an Ar atmosphere). Ti-6Al-4V ELI alloy tensile specimens in both the horizontal (i.e., X and Y) and vertical (Z) directions were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 55 publications
(75 reference statements)
3
29
0
Order By: Relevance
“…In this scenario, not only the influence the α laths coarsening but also the , as reported by Wycisk et al [ 301 ], who showed a α laths coarsening from ~1 μm to 4 μm. The same results are shown by Mahmud et al [ 111 ], who reported a linear increase with time. To avoid an excessive grain coarsening, Herzog et al [ 302 ] proposed an increase in pressure to 200 MPa and a consequent decrease in temperature up to 820 °C.…”
Section: L-pbfed Ti6al4v: Microstructuresupporting
confidence: 88%
See 4 more Smart Citations
“…In this scenario, not only the influence the α laths coarsening but also the , as reported by Wycisk et al [ 301 ], who showed a α laths coarsening from ~1 μm to 4 μm. The same results are shown by Mahmud et al [ 111 ], who reported a linear increase with time. To avoid an excessive grain coarsening, Herzog et al [ 302 ] proposed an increase in pressure to 200 MPa and a consequent decrease in temperature up to 820 °C.…”
Section: L-pbfed Ti6al4v: Microstructuresupporting
confidence: 88%
“…In this scenario, the as-built sample formed by a fully α′ martensite structure does not show any portion of the β-phase in the XRD spectrum, as shown in Figure 34 . The same results are illustrated by [ 111 , 223 , 224 , 225 ]. On the other hand, increasing the presence of the α + β phase, the XRD spectrum starts showing small peaks related to the β-phase, as highlighted in the red spectrum related to the Ti6Al4V stress-relieving sample.…”
Section: L-pbfed Ti6al4v: Microstructuresupporting
confidence: 73%
See 3 more Smart Citations